2022
DOI: 10.1007/s10534-022-00459-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in vitro gastrointestinal digestion on the antibacterial activity of bioactive dairy formulas supplemented with lactoferrin against Cronobacter sakazakii

Abstract: Milk is a source of proteins with high nutritional value and relevant biological activities. Bioactive milk proteins, like lactoferrin, are important for newborn development and can also be used as ingredients in functional products to improve health. Lactoferrin is essential in infant’s diet, since protects against infections and promotes immune system maturation. Bovine lactoferrin is used to supplement formula milk in order to strengthen baby’s defences against some pathogenic bacteria. Thus, lactoferrin su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…To obtain whey and buttermilk, raw bovine milk was provided by Villacorona (El Burgo de Ebro, Spain), and processed at the Food Science and Technology Pilot Plant of the University of Zaragoza, as detailed previously. [ 20 ] Formula 1 (F1) was prepared with a whey base, supplemented with nLF and MFGM. For its preparation, freeze‐dried whey was rehydrated, taking into account its dry matter (0.068 g mL −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…To obtain whey and buttermilk, raw bovine milk was provided by Villacorona (El Burgo de Ebro, Spain), and processed at the Food Science and Technology Pilot Plant of the University of Zaragoza, as detailed previously. [ 20 ] Formula 1 (F1) was prepared with a whey base, supplemented with nLF and MFGM. For its preparation, freeze‐dried whey was rehydrated, taking into account its dry matter (0.068 g mL −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Raw bovine milk was supplied by the dairy company Villacorona (El Burgo de Ebro, Spain). The quality of milk was verified after reception by checking the pH, acidity, fat percentage, and alkaline phosphatase and lactoperoxidase activities, and it was processed as explained in a previous study [28] at the Food Science and Technology Pilot Plant of the University of Zaragoza, located in the Veterinary Faculty. The whey and BM obtained were lyophilized and kept at −20 • C for later use.…”
Section: Chemicals and Preparation Of Milk Samplesmentioning
confidence: 99%
“…In this special issue, Conte et al ( 2022 ) demonstrated that bLf can effectively inhibit cystitis caused by Escherichia coli , owing to competitive binding between the cationic bLf and anionic components of the host cells; this in turn may hide bacterial entrance sites and thereby inhibit bacterial invasion of the cells. Abad et al ( 2022 ) reported that in vitro gastrointestinal digestion of bLf actually promoted the antibacterial activity of infant formulas that were supplemented with lactoferrin against Cronobacter sakazakii . This bacterium was selected for this study, as it is extremely resistant to dry conditions and it has been identified in previous studies as the source of infections in infants originating from contaminated powdered infant formula.…”
mentioning
confidence: 99%